Collaborative research and multi-issue movement building for educational justice: Reflections on the Urban Research Based Action Network (URBAN) - Mark R. Warren; Ronald David Glass (Arizona State University, 2019)
Two long-time scholar-activists reflect on a distinctive approach to research that they call collaborative research for justice, research that is conducted with community leaders and education activists to advance equity and social justice. They argue that by linking research directly with action this kind of research has the power to speak directly to the current crises not only in education, but also in the other institutions of civil society. Drawing on decades of experience in public research universities, local community based organizations, inter/national disciplinary research organizations, and distributed informal networks of engaged scholars, social justice activists, and community leaders, they reflect specifically on the more recent formation of the Urban Research Based Action Network (URBAN), a national network of people enacting a variety of forms of collaborative research for justice, now with more than 1500 members. They outline lessons that might contribute to building the multi-issue movement for educational justice that they believe is required to transform public schools to make them serve the needs of the most disadvantaged, aggrieved, and inequitably treated communities. In its short history URBAN has already impacted the academy through the gatherings and meetings it has hosted as well as through a rigorous publishing agenda, including a special issue of EPAA in which this article appears.